Efeito da aplicação de silicato de cálcio no crescimento, no estado nutricional e na produção de matéria seca de mudas de maracujazeiro - Prado, Renato De M. [UNESP]; Natale, William (Departamento de Engenharia Agrícola - UFCG, 2005)
This work was carried out with the objective of evaluating the effect of the addition of industrial residue (calcium silicate) to the substrate in the production of the passion fruit seedlings, studying the benefits in the development, the production of dry matter and the nutritional state of the plants. The experimental design adapted was a randomized block with 5 treatments and 4 repetitions. The doses of calcium silicate applied were equivalent to raise in half; one; one and half; and twice the dose to elevate percentage of base saturation = 50%, corresponding to the 0; 0.45; 0.90; 1.35 and 1.80 g per pot, respectively, besides a control without application. The experimental unit was constituted of pots with 2 dm³ of a Red Latossol (Oxisol). After 80 days of the plantation, the height, stem diameter, number of leaves and the dry matter of the shoot and the root, as well as contents of macro and micronutrients were evaluated. The passion fruit seedlings responded to the calcium silicatie application. The maximum development was associated with the base saturation of 58% with the concentrations of Ca in the soil equivalent to19 mmol c dm-3 and the content of Ca in the shoot of 12.0 g kg-1.

Objetivou-se, com este trabalho, avaliar os efeitos da aplicação de um resíduo industrial (silicato de cálcio) ao substrato de produção das mudas de maracujazeiro, como material corretivo, no desenvolvimento, na produção de matéria seca e no estado nutricional das plantas. O delineamento experimental foi em blocos ao acaso, com cinco tratamentos e quatro repetições. As doses de silicato de cálcio foram aplicadas objetivando-se elevar a percentagem de saturação com bases 25, 50, 75 e 100%, correspondendo a 0,45; 0,90; 1,35 e 1,80 g por vaso, respectivamente, além da testemunha sem aplicação. A unidade experimental foi constituída por vasos com 2 dm³ de substrato de um Latossolo Vermelho distrófico. Após 80 dias da semeadura avaliaram-se: a altura, o número de folhas, o diâmetro do caule e a matéria seca da parte aérea e das raízes e, também, os teores de macro e micronutrientes. O resíduo de silicato de cálcio mostrou-se como corretivo de acidez do solo e como fonte de Ca, embora ineficiente fonte de Mg. O maior crescimento das mudas de maracujazeiro esteve associado à saturação por bases do solo de 58%, à concentração de Ca do solo de 19 mmol c dm-3 e teores de Ca na parte aérea de 12,0 g kg-1.
Effect of application of calcium silicate on growth, nutritional status and dry matter production of passion fruit seedlings
Keywords: liming; acidity; Passiflora edulis; calagem; acidez; Passiflora edulis